Optimizing staging of Meniere’s disease: integrating electrocochleography with vestibular tests - Huang, Muchen; Wang, Xianren; Chen, Minqi (Frontiers in Neuroscience, 2025)
ObjectivesThis study aimed to evaluate the diagnostic and staging efficacy of integrating electrocochleography (ECochG) with vestibular function tests—specifically cervical and ocular vestibular evoked myogenic potentials (cVEMP and oVEMP), caloric test (CT), and video head impulse test (vHIT)—for Ménière’s disease (MD).DesignData were collected from 54 MD patients (66 affected ears) admitted to a hospital between January 2023 and January 2024. Each participant underwent pure tone audiometry, ECochG, cVEMP, oVEMP, CT, and vHIT. The results were compared against both established clinical criteria and a newly proposed staging system. Inclusion criteria followed the 2015 diagnostic guidelines for MD. Statistical analyses, including ANOVA, Chi-square, and Kruskal–Wallis H tests, were conducted, and a random forest model was employed to validate the robustness of the proposed staging system.ResultsThe novel staging system, incorporating vestibular function tests, demonstrated superior sensitivity and diagnostic accuracy compared to traditional audiometry-based staging. Early-stage MD detection improved significantly, with vestibular test abnormalities strongly correlating with disease progression. The overall positive rate for any test was 98.5%. ECochG abnormalities were detected in 54.5% of cases, while cVEMP and oVEMP abnormalities were observed in 75.8% and 69.7% of cases, respectively. The new staging system exhibited a stronger correlation with vestibular dysfunction, effectively identifying functional impairment prior to significant hearing loss.ConclusionThe integration of ECochG with vestibular function tests provides a more comprehensive diagnostic framework for MD. This multimodal approach enhances early detection, improves staging accuracy, and offers deeper insights into disease progression, thereby facilitating more personalized treatment strategies.